DEVELOPMENT OF LEARNING MEDIA "SMART WINDOW" TO ENHANCE CHILDREN'S COGNITIVE ABILITIES - Entri Mardiyanti; Erna Budiarti (International Journal of Teaching and Learning, 2026)
This research aims to develop smart window media to enhance the cognitive abilities of children in group B at RA Baitul Maal. The research method used is research and development (R&D) with a qualitative and quantitative (mixed methods) approach based on the ADDIE development model. Data is collected through observations and interviews conducted with teachers and children at RA Baitul Maal. The research findings indicate that this smart window media is designed to meet the needs of early childhood by integrating engaging, safe, and developmentally appropriate visual and manipulative elements. The feasibility of the "Smart Window" media: Based on expert validation, this media is deemed feasible with a total score of 83.59, which falls into the "Very High" category. This media meets the criteria of usability, design, and aesthetics, and is capable of fostering children's curiosity and motivation to learn. Children's Cognitive Abilities After Intervention: Post-test results show a significant improvement in children's cognitive abilities. All children experienced an improvement in developmental category from "Not Developing" or "Still Developing" to "Developing as Expected" or "Developing Very Well." The average score increase of 45.03 percent indicates the effectiveness of this media in supporting children's cognitive development.